Personally Speaking: Why I hate war and oppose pacifism (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
I protest against the naïve pacifist stance against the war in Ukraine because it fails to understand that a lack of support for a nation that defends itself may lead to mass killings, torture, rape and other traumatic experiences. Lithuania witnessed it all after the Soviets occupied it.
Keywords: War; pacifism; occupation; trauma; Ukraine; Lithuania